Effect of liver and renal dysfunction on circulating methionine-enkephalin immunoreactivity. - Smith, R; Grossman, A; Gimson, A; Besser, G; Rees, L (1985)
Plasma methionine-enkephalin (Met-Enk) immunoreactivity has been determined in 24 patients with varying degrees of renal impairment and 14 patients with hepatic failure. Plasma Met-Enk immunoreactivity correlated inversely with creatinine clearance (r = -0.71, P less than 0.001) but was not affected by even severe hepatic failure in the absence of renal impairment. In two patients, with renal failure and elevated plasma prolactin, administration of naloxone (16 mg) had no effect on circulating prolactin concentrations. These studies indicate that the kidney has a major role in Met-Enk metabolism while the liver does not, and further suggest that elevated circulating endogenous opiates are not responsible for the increased production of prolactin found in renal failure.